Nitrate signaling and the control of Arabidopsis growth and development. (February 2019) - Fredes, Isabel; Moreno, Sebastián; Díaz, Francisca P; Gutiérrez, Rodrigo A
Highlights: Local and systemic N signaling modulates a variety of developmental programs. Nitrate breaks seed dormancy reducing abscisic acid levels. Cross-talk between nitrate and cytokinin signaling influences meristem dynamics. Local and systemic signaling controls shoot and root architecture. Nitrate delays flowering time via the gibberellin signaling pathway. Abstract : Coordination between plant development and nutrient availability ensures a suitable supply of macromolecules for growth and developmental programs. Nitrate is an important source of nitrogen (N) that acts as a signal molecule to modulate gene expression, physiological, growth and developmental responses throughout the life of the plant. New key players in the nitrate signaling pathway have been described and knowledge of the molecular mechanics of how it impacts growth and developmental processes is increasing fast. Importantly, mechanisms for nitrate-control of growth and developmental processes have been proposed for both local as well as systemic responses. This article provides a synthesis of recent insights into molecular mechanisms by which nitrate impacts growth and development over Arabidopsis life-cycle.